PENGARUH INFLASI DAN INVESTASI TERHADAP TINGKAT PENGANGGURAN TERBUKA DI INDONESIA PERIODE 2002-2019 - Putri Sari MJ Silaban; Stevi Jesika Siagian (Niagawan, 2021)
Open Unemployment is a labor force that truly does not have a job. This study was conducted aiming to examine the effect of inflation and investment on open unemployment in Indonesia from 2002 to 2019. The data used are time series data. The analysis technique used in this study is the classical assumption testing, hypothesis testing and multiple regression analysis. The analysis shows that partially positive and significant effect on open unemployment means that the higher the inflation, the higher the open unemployment will be, and vice versa. Investment is partially negative and significant effect on open unemployment means that the higher the investment, the open unemployment will decrease, and vice versa. And inflation and investment simultaneously have a significant effect on open unemployment. The results can be expected to provide input to the government so that it can maintain a stable inflation and investment rate so that the level of open unemployment can remain stable.Keywords: Inflation, Investment, and Open Unemployment.